Development and validation of self-perceived employability instrument for undergraduate students in private higher education institutions - Wong, Siew Ping (2020)
The unemployment issue among university graduates in Malaysia remains unresolved. Universities play a vital role in dealing with this problem as one of the main functions of tertiary education is to produce graduates with employability to join the competing job market. It is necessary to study undergraduate students’ perceived employability as it portrays students’ willingness to change and adapt to possible working environments. However, there is a lack of psychometrically tested students’ self-perceived employability instrument in Malaysian context. This study aims to identify students’ conceptualization of employability, and develop a valid and reliable instrument to measure undergraduate students’ selfperceived employability. A mixed method research design and purposive sampling involving two private universities in Selangor were applied. With a qualitative approach, randomly selected final-year undergraduate students in a private university were interviewed to explore students’ conceptualization of employability and their employability attributes. Employability models were reviewed and a theoretical model of five-factor was proposed. A total of 113 items were written for Self-Perceived Employability Instrument based on the literature and the qualitative findings. Through content validation, items were amended based on the experts’ feedback, resulted in 112 items. A quantitative approach was conducted in another private university. Random sampling was applied and two groups of sample were determined for factor analyses. In exploratory factor analysis, 112 items were reduced to 33 items in seven factors, namely career resilience, human and social capital, teamwork, conscientiousness, critical thinking, academic, and leadership. Confirmatory factor analysis confirmed the seven-factor model. Construct validity provided more psychometric properties of the instrument. The reliability of the instrument was also proven. Self-perceived Employability Instrument is useful to reflect finalyear undergraduate students’ job readiness and the effectiveness of the higher education institutions in producing graduates with high employability. However, the usage of the instrument might be limited to private university students.